Ketogenic Diet Suppresses Alcohol Withdrawal Syndrome in Rats. (23rd December 2017) - Dencker, Ditte; Molander, Anna; Thomsen, Morgane; Schlumberger, Chantal; Wortwein, Gitta; Weikop, Pia; Benveniste, Helene; Volkow, Nora D.; Fink‐Jensen, Anders
Abstract : Background: Alcohol use disorder is underdiagnosed and undertreated, and up to 50% of alcohol‐abstinent patients diagnosed with alcohol dependence relapse within the first year of treatment. Current treatments for the maintenance of alcohol abstinence in patients with alcohol use disorder have limited efficacy, and there is an urgent need for novel treatment strategies. Decreased cerebral glucose metabolism and increased brain uptake of acetate were recently reported in heavy drinkers, relative to controls. Given the switch of metabolic fuel from glucose to acetate in the alcohol‐dependent brain, we investigated the potential therapeutic benefit of a ketogenic diet in managing alcohol withdrawal symptoms during detoxification. Methods: Male Sprague Dawley rats fed either ketogenic or regular diet were administered ethanol or water orally, twice daily for 6 days while the diet conditions were maintained. Abstinence symptoms were rated 6, 24, 48, and 72 hours after the last alcohol administration. Results: Maintenance on a ketogenic diet caused a significant decrease in the alcohol withdrawal symptoms' "rigidity" and "irritability." Conclusions: Our preclinical pilot study suggests that a ketogenic diet may be a novel approach for treating alcohol withdrawal symptoms in humans. Abstract : The potential therapeutic benefit of a ketogenic diet in managing alcohol withdrawal symptoms during detoxification was investigated. Rats fed either ketogenic or regular diets were administered ethanol or water orally, and abstinence symptoms were rated after the last alcohol administration. Maintenance on a ketogenic diet caused a significant decrease in the alcohol withdrawal symptoms 'rigidity' and 'irritability', suggesting that a ketogenic diet may be a novel approach for treating alcohol withdrawal symptoms in humans.